Corporate Culture, Strategic Orientation, and Business Performance: New Approaches to Modeling Complex Relationships - Hynes, Niki (Elsevier Inc., 2009)
This paper introduces the idea of using a complex biochemical model as an alternative methodfor modeling managerial constructs in order to incorporate change within organizations. Toillustrate the potential of using this type of modelling, two well established managerialconcepts (strategic orientation and corporate culture) are reviewed and the differences andsimilarities between the constructs discussed. Traditional simplistic models are presented andthe limitations of these for dealing with change within and between organizations arediscussed. A more complex model based on enzyme action is presented, and integrated withcase study material which allows rich, complex and dynamic modeling including theincorporation of evolutionary and co-evolutionary change within organizations.